Porous One‐Dimensional Nanomaterials: Design, Fabrication and Applications in Electrochemical Energy Storage. Issue 20 (20th January 2017) - Wei, Qiulong; Xiong, Fangyu; Tan, Shuangshuang; Huang, Lei; Lan, Esther H.; Dunn, Bruce; Mai, Liqiang
Abstract : Electrochemical energy storage technology is of critical importance for portable electronics, transportation and large‐scale energy storage systems. There is a growing demand for energy storage devices with high energy and high power densities, long‐term stability, safety and low cost. To achieve these requirements, novel design structures and high performance electrode materials are needed. Porous 1D nanomaterials which combine the advantages of 1D nanoarchitectures and porous structures have had a significant impact in the field of electrochemical energy storage. This review presents an overview of porous 1D nanostructure research, from the synthesis by bottom‐up and top‐down approaches with rational and controllable structures, to several important electrochemical energy storage applications including lithium‐ion batteries, sodium‐ion batteries, lithium‐sulfur batteries, lithium‐oxygen batteries and supercapacitors. Highlights of porous 1D nanostructures are described throughout the review and directions for future research in the field are discussed at the end. Abstract : Porous 1D nanomaterials utilize the advantages of both 1D nanoarchitecture and porous morphology to further enhance the performance of materials for energy‐storage applications. The current status of porous 1D nanostructures, from methodologies for rational and controllable synthesis, to their successful application in lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium–oxygen batteries and supercapacitors is presented.